A series of fluorinated phenylpyridine-based electron-transporters for blue phosphorescent OLEDs. Issue 5 (12th January 2016) - Kamata, Takahiro; Sasabe, Hisahiro; Watanabe, Yuichirio; Yokoyama, Daisuke; Katagiri, Hiroshi; Kido, Junji
Abstract : A series of fluorinated phenylpyridine-based electron-transport materials were developed and the influence of fluorine atom(s) on molecular orientation and mobility was investigated. Abstract : A series of fluorinated phenylpyridine-based electron-transport materials (ETMs) for organic light-emitting devices (OLEDs) based on 3, 5, 3′′, 5′′-tetra-3-pyridyl-[1, 1′;3′, 1′′]terphenyl (B3PyPB ) were developed, and the influence of fluorine atom(s) in the core skeleton on their physical properties, such as molecular orientation, electron-transport and electron-injection, was investigated. The monofluorinated ETM exhibited a relatively large orientation order parameter of −0.23 and an electron mobility of 10 −3 cm 2 V −1 s −1, which was 10 times higher than that of its nonfluorinated counterpart because of concerted intermolecular interactions involving not only the CH⋯N hydrogen bonds but also the aromatic fluorine atoms, in addition to π–π stacking. Surprisingly, the difluorinated ETM exhibited a smaller molecular orientation order parameter than the mono- and nonfluorinated ETMs, likely because of the poor intermolecular interactions between the fluorine atoms and nitrogen lone pairs. Blue phosphorescent OLEDs fabricated using the monofluorinated ETM had a low operation voltage of 3.5 V at 1000 cd m −2 .